Fundus autofluorescence of choroidal nevus and melanoma. Issue 10 (12th April 2007) - Lavinsky, Daniel; Belfort, Rubens N; Navajas, Eduardo; Torres, Virginia; Martins, Maria Cristina; Belfort, Rubens
Abstract : Background: To describe autofluorescence patterns of choroidal melanocytic lesions using the Heidelberg Retinal Angiograph 2 system (HRA2). Methods: 20 patients with choroidal melanocytic lesions in the ocular fundus underwent ophthalmologic examination, fundus photography, autofluorescence and optical coherence tomography (OCT). Pathologic examination was performed on one enucleated eye with a large choroidal melanoma. Results: 15 patients had choroidal nevi and 5 had malignant choroidal melanoma (1 small, 1 medium and 3 large tumours). Choroidal nevi did not show any characteristic autofluorescence pattern, although secondary retinal pigment epithelium (RPE) changes, such as drusen and pigment epithelium detachment, appeared faintly hyperautofluorescent in 2 patients. Only the small malignant choroidal melanomas had prominent orange pigmentation, although all melanomas had an intense confluent hyperautofluorescent signal over the lesions. Pathology of one large malignant melanoma revealed lipofuscin underlying RPE. Conclusion: Most nevi did not have characteristic hyperautofluorescent features, but choroidal melanomas seemed to have a pattern of confluent hyperautofluorescence. Therefore, autofluorescence may be a useful non-invasive tool to assess lipofuscin in pigmented choroidal lesions, which may contribute to the diagnosis of malignancy. This hypothesis, however, remains to be confirmed in large prospective studies.